2015
DOI: 10.1200/jco.2014.60.0890
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Significance of Secondary and Therapy-Related Acute Myeloid Leukemia: A National Population-Based Cohort Study

Abstract: Our results support that de novo AML, sAML, and tAML are biologically and prognostically distinct subtypes of AML. Patients with non-MDS-sAML have dismal outcomes, independent of age and cytogenetics. Previous myeloid disorder, age, and cytogenetics are crucial determinants of outcomes and should be integrated in treatment recommendations for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
221
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(241 citation statements)
references
References 36 publications
17
221
2
1
Order By: Relevance
“…This enables and encourages the physicians to enroll intensive therapy eligible patients with comorbidity into these trials and permits readily translation of clinical trial results to broader AML cohorts. Similar to previously observed, presence of sAML or tAML negatively impacted enrollment into clinical trials, [12] at least in part, due to risk of excessive anthracycline exposure. These findings limit our understanding on therapeutic effects in these subgroups of patient, when only focusing on clinical trial results.…”
Section: Discussionsupporting
confidence: 83%
“…This enables and encourages the physicians to enroll intensive therapy eligible patients with comorbidity into these trials and permits readily translation of clinical trial results to broader AML cohorts. Similar to previously observed, presence of sAML or tAML negatively impacted enrollment into clinical trials, [12] at least in part, due to risk of excessive anthracycline exposure. These findings limit our understanding on therapeutic effects in these subgroups of patient, when only focusing on clinical trial results.…”
Section: Discussionsupporting
confidence: 83%
“…This result is slightly higher than the incidence reported by the Danish and Swedish registries and by the German-Austrian AMLSG group [11, 13, 18]. …”
Section: Discussioncontrasting
confidence: 54%
“…Intensive chemotherapy in patients with AML secondary to previous MDS, CMML, MPN, or prior cytotoxic exposure remains unsatisfactory compared to de novo AML [13, 19]. However, our results suggest that t-AML following treatment of solid cancer has a better outcome compared to post-MDS, post-CMML, and post-LD while post-MPN AML seems to have the worst outcome.…”
Section: Discussionmentioning
confidence: 76%
“…Compared to patients with de novo AML, t-MN patients are more likely to have high-risk karyotypes, comorbidities, and poor performance status 130 . In a study that adjusted for these confounding factors, it was found that among patients 60 years or older, with a high-risk karyotype, and undergoing intensive therapy, t-MN patients had a similar outcome compared to de novo AML 130 .…”
Section: Prognosismentioning
confidence: 99%